PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING DI KELAS V SDN 12 SALIMPAT KABUPATEN SOLOK - Eska Nugraha, Citra; Zuryanty; Fitria, Yanti; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Natural and Social Sciences (IPAS) is one of the subjects in the independent curriculum that requires the activeness and critical thinking skills of students. However, in practice, social studies learning in elementary schools is still dominated by teachers and the lack of activities that actively involve students, thus having an impact on students' learning outcomes is low. The purpose of this research is to improve students' learning outcomes in science learning through the application of the Problem Based Learning (PBL) model in grade V of SDN 12 Salimpat, Solok Regency. This type of research is Classroom Action Research (PTK) which is carried out in two cycles, using qualitative and quantitative approaches. The subjects of this research are classroom teachers and class V students totaling 21 people. The data collection techniques used are tests, non-tests and observations. The results of the study show that the application of the Problem Based Learning model can improve student learning outcomes. The average assessment of teaching modules increased from 88,3% (good) to 97.2% (very good). Teacher activity increased from 89.3% (good) to 96.4% (very good), while student activity increased from 89.3% (good) to 96.4% (very good). Then the activities of student learning outcomes also increased on average from cycle I 73.1 (adequate) to 89.6 (good) in cycle II. Thus, the Problem Based Learning model is effectively used in improving the learning outcomes of IPAS in elementary schools.